PECULIARITIES OF NEUROENDOCRINE REGULATION DURING STRESS IN TEENAGE GIRLS WITH HYPERANDROGENIC SYNDROME - A. V. Moskovkina; V. A. Linde; O. Z. Puzikova (Медицинский вестник Юга России, 2013)
Purpose: To reveal peculiarities of neuroendocrine regulationduring psychoemotional stress and their role in the formation of menstrual dysfunction in girls of puberty age with hyperandrogenism.Materials and methods.In 84 patientsattheageof 15-17 withdifferentmanifestations of hyperandrogenism and in 30 girls of the corresponding age without manifestations of hyperandrogenism the content of basal and stress level of dopamine, androgens, gonadotropic hormones and sex steroids in blood was studied in the course of mild intellectual and emotional stress.Results: Considerable differences in the level of basal and stress dopamine in the patients with hyperandrogenism in comparison with control group were revealed. In the girls with hyperandrogenism and menstrual disorders as compared to the patients without menstrual dysfunction more greatly expressed disorders of dopamine secretion were observed; they manifested themselves in the form of reliable increase in its basal level as well as reliable change in its secretion in response to the caused stress. A reliable direct correlation of the dopamine level with the excess secretion of adrenal androgens, adrenocorticotropic hormones and luteinizing hormones, and inverse correlation – with the level of estradiol were determined that indicated pathogenetic connection between stress hormones and a number of components of neuroendocrine regulation of reproductive system.Summary: The results of the conducted research confirm an important role of neuroendocrine regulation disturbances during stress in the genesis of ovarian dysfunction formation in case of hyperandrogenic syndrome.